Utilization of the My ADA Application for ANC Visits for Pregnant Women in the City of Bengkulu - Yuniarti Yuniarti; Elvi Destariyani; Nurniati Tianastia; Rahmadona Rahmadona (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Antenatal care (ANC) plays an important role in the early detection and prevention of complications during pregnancy, childbirth, and the postpartum period. However, ANC utilization in Indonesia, including Bengkulu City, remains below the expected standard. Limited maternal knowledge and the less optimal use of conventional educational media, such as the Maternal and Child Health (KIA) book, contribute to low ANC attendance. Therefore, innovative digital-based educational media, such as the My ADA application, are needed to improve ANC utilization among pregnant women. This quantitative study employed a quasi-experimental design with a pretest–posttest two-group approach. The study was conducted at independent midwifery practices in Bengkulu City. A total of 50 second-trimester pregnant women who met the inclusion criteria were selected using purposive sampling and divided into two groups: the My ADA application intervention group and the KIA book comparison group. Data were collected before and after the intervention using structured questionnaires and ANC visit records. Statistical analysis was performed using appropriate parametric and non-parametric tests after normality testing with the Shapiro–Wilk test. The results demonstrated a statistically significant difference in ANC utilization and visit frequency between the intervention and comparison groups (p < 0.05). Pregnant women who used the My ADA application showed greater improvement in ANC utilization and higher ANC visit frequency compared to those who used the KIA book. The findings indicate that the My ADA application is more effective than conventional KIA book media in improving ANC utilization among second-trimester pregnant women. Digital health applications can be utilized as alternative educational and monitoring tools to support maternal health services and enhance adherence to antenatal care visitsKeyword : My ADA application, antenatal care, Pregnant women, Health technology, Maternal health, ANC utilization